ANALISIS KESULITAN MAHASISWA MENGHAFAL NAMA-NAMA LATIN DI PROGRAM STUDI PENDIDIKAN BIOLOGI ANGKATAN 2014 FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS MUHAMMADIYAH PAREPARE - Amri Amri; Jusmiati Jafar (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2016)
The research was conducted at the University of Muhammadiyah Parepare the Faculty of Education Biology Education Studies Program Specifically Force 2014. The research used quantitative descriptive research type. Subjects of this study Latin names while the object of this study are students. Further data are obtained by using a structured interview and documentation. Then the data were analyzed using descriptive analysis techniques. The results of this study indicate that: (i) a description of the student's knowledge of Biology Education 2014 Forces of Latin names can be said that the students had difficulty in memorizing the Latin names. It can be seen on the picture of the student's knowledge of Latin names, the average percentage of correct answers as much as 40.24% and the percentage of wrong answers as much as 57.76%. (Ii) a description of the difficulties faced by students in memorizing the Latin names in Biology Education Studies Program Force 2014 is the complicated pronunciation answered by 39 students from 52 students with a percentage of 75%. While more dominant for many groupings of Latin names were answered by 50 students from 54 students with a percentage of 96.2%. As for the memjawab that trouble memorizing the Latin names due to the low recall that 30 students from 52 the number of students with a percentage of 57.7%. (Iii) Methods of Biology Education Students Force 2014 in memorizing Latin names are repeated with a percentage of 86.5% and 57.7% make keyword.